Review of behavioral activation for depression: A clinician's guide - Mazzucchelli, Trevor (Australian Academic Press Pty Ltd, 2010)
Reviews the book, Behavioral activation for depression: A clinician's guide by Christopher R. Martell, Sona Dimidjian, and Ruth Herman-Dunn. The authors have elaborated upon, revised, and in some places simplified their behavioral activation treatment approach, as it was described by Martell et al. (2001). The result is a practical and usable guide for clinicians. The authors begin with a review of the origins of the present range of BA interventions and similar behaviour therapies. Subsequent chapters review core principles of BA, how the therapy is structured, and the general style of the BA therapist. Ideas and suggestions for presenting the BA conceptualisation of depression are provided along with suggested responses to frequently asked questions. The authors present a very accessible summary of relevant behaviour theory along with guidelines and procedures for assessing and understanding patterns in clients behaviour. They have certainly delivered a highly practical and accessible book that will be useful either for clinicians wanting to deliver this well-established treatment approach for depression or to expand their use of behavioural principles within other models of treatment.